Lessons from internship programme: a study of sociology and anthropology students at IIUM - Mohamad Diah, Nurazzura; Mustari, Sohela (2015)
Many universities require their undergraduate students to undergo an internship programme to equip them with the working experience necessary in making them better prepared for the job market. Keeping this in mind, the Department of Sociology and Anthropology (SOCA) at IIUM introduced an internship programme in Semester 3, 2008/2009 to their undergraduate students as part of their graduation requirement. This study was directed to gather information on the experience that the students had gained in their workplace and the difficulties and benefits they had achieved through this exercise. A survey was conducted to gather essential data from 99 Sociology and Anthropology students who had already accomplished their three-month internship either in the public or private sector. Data were analyzed using SPSS. Findings from this study clearly show that despite some barriers in their workplace environment, the students were satisfied with their internship as it added some opportunities. More importantly, the basic challenge that the interns faced was the lack of knowledge employers had about the Sociology and Anthropology and its practical aspect. However, despite this, these students were welcomed by both private and public organizations. In general, this research has shown that internship for social sciences students is seen as a platform to increase employability among undergraduates. Certainly, there is great opportunity for students particularly from a less popular discipline to utilize the internship programme to equip themselves with the real knowledge of the tasks involved in various job prospects.